STRATEGI PEMBANGUNAN DESA WISATA DENGAN MENGEMBANGKAN UNIT UMKM PADA PEMANFAATAN SUMBER DAYA LIMBAH LINGKUNGAN - Jumaidi, Lalu Takdir; Iman Waskito; Baiq Anggun Hilendri L.; Victoria Kusumaningtyas; Novi Rizki (Jurnal Pepadu, 2023)
Waste is a crucial problem to date, every day there are tons of waste produced by humans and most of it is household waste. A lot of waste comes from factories, plastic waste and household waste such as food scraps and leftover pieces of vegetables and fruit, so more effective and environmentally friendly handling is needed. The method used is waste processing using takakura baskets, an option and innovation that is easy to put into practice on a household scale and is a solution for handling waste, and can even have economic value. The aim of this community service is so that the village community can know how to make organic fertilizer using household/kitchen waste using the takakura method which can ultimately be directed towards advancing MSMEs engaged in the field of utilizing waste into organic fertilizer. The partner for this community service is Lantan Village, North Batukliang District. The service method is carried out by providing education about waste management followed by practicing how to process organic waste into fertilizer using the takakura method.